Nehru’S Art of Autobiography Writing: Exploring the Depths of Self in Autobiographical Literature (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Autobiography is an important genre of literature.  Great men and thinkers of the world havewritten autobiographies in order to reveal various facets of theirpersonality.  What fascinates a man mostis his own self?  Sir John Davies hasrightly said: